IMPLEMENTASI MODEL PEMBELAJARAN RECIPROCAL TEACHING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR - Sutrisni Andayani (UNIVERSITAS MUHAMMADIYAH METRO, 2016)
This research objectives to determine whether the use of learning strategies of Reciprocal Teaching can improve students' critical thinking skills and learning outcomes in the real analysis I material. This research is Classroom Action Research using Reciprocal Teaching with four key activities, namely questioning, clarifying, predicting, and summarizing/review, with the stages include: planning, implementation, monitoring and reflection carried out in two cycles. This research was carried out on the mathematics education at the Muhammadiyah University of Metro, Lampung. The technique of collecting data through observation, questionnaires, interviews, and tests. The results of critical thinking skills increase of 32.3 from the prior cycle by 45.7 becomes 78.0 at the end of the cycle. Learning outcomes increase at 33.4 (3.21 pretest and posttest 65.5) in the first cycle and 37.0 (35.4 pretest and posttest 72.4) in the second cycle. Therefore, this research can be concluded that Reciprocal Teaching Model can improve the students' critical thinking skills and learning outcomes